The French lieutenant's woman [videorecording (DVD)] - Streep, Meryl; Irons, Jeremy, 1948-; McKern, Leo, 1920-2002 (Criterion collection, 2015)
A parallel narrative of a Victorian-era gentleman and the social outcast he risks everything to love, and of the contemporary actors cast in those roles and immersed in their own forbidden affair.